2022
DOI: 10.26434/chemrxiv-2021-d2ksx-v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting the future of excitation energy transfer in light-harvesting complex with artificial intelligence-based quantum dynamics

Abstract: Exploring excitation energy transfer (EET) in light-harvesting complexes (LHCs) is essential for understanding the natural processes and design of highly-efficient photovoltaic devices. LHCs are open systems, where quantum effects may play a crucial role for almost perfect utilization of solar energy. Simulation of energy transfer with inclusion of quantum effects can be done within the framework of dissipative quantum dynamics (QD), which are computationally expensive. Thus, artificial intelligence (AI) offer… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 43 publications
(64 reference statements)
0
27
0
Order By: Relevance
“…Similarly, we have recently demonstrated that for some known asymptotic limits, ML can be trained to predict quantum dynamics up to the infinite future time, but this was done only for a model Hamiltonian and not for nuclear positions. 28 Predictions made with the 4D-A 2 I model for H2 are practically instantaneous while propagating sequential BOMD of even such a small system as H2 up to 15 fs with 3D-MLP and a small time-step of 0.005 fs took longer than 30 min; propagating with full configuration interaction QM method would take several months on a desktop computer (see Methods). The ultimate goal of a complete 4D-A 2 I model is to describe an atomistic system across infinite 4D spacetime, i.e., predict dynamics trajectories for any combination of initial conditions and any time.…”
Section: Learning 4d Spacetime Of a Hydrogen Moleculementioning
confidence: 99%
“…Similarly, we have recently demonstrated that for some known asymptotic limits, ML can be trained to predict quantum dynamics up to the infinite future time, but this was done only for a model Hamiltonian and not for nuclear positions. 28 Predictions made with the 4D-A 2 I model for H2 are practically instantaneous while propagating sequential BOMD of even such a small system as H2 up to 15 fs with 3D-MLP and a small time-step of 0.005 fs took longer than 30 min; propagating with full configuration interaction QM method would take several months on a desktop computer (see Methods). The ultimate goal of a complete 4D-A 2 I model is to describe an atomistic system across infinite 4D spacetime, i.e., predict dynamics trajectories for any combination of initial conditions and any time.…”
Section: Learning 4d Spacetime Of a Hydrogen Moleculementioning
confidence: 99%
“…Recently, ML has been successfully applied to accelerate dynamics propagation of open quantum systems. [10][11][12][13][14][15][16][17][18][19] ML-based approaches adopted in the literature so far, can be divided into two categories: recursive [13][14][15][16] and non-recursive [17,18] approaches. ML-based recursive approaches are quite successful but there are some downsides of them; first, iterative propagation is inherently slow and may lead to error accumulation and second, they need a short time-trajectory generated with traditional quantum dynamics methods.…”
mentioning
confidence: 99%
“…[17] Recently, we have proposed an alternative non-recursive, artificial intelligence-based quantum dynamics (AI-QD), approach learning dynamics trajectories as a function of time and simulation parameters, the reorganization energy λ, characteristic frequency γ, and temperature T . [18] This makes all time-steps independent from each other which allows us to predict system's state at any arbitrary time, without the need of propagating the trajectory.…”
mentioning
confidence: 99%
See 2 more Smart Citations